Preparation of Biochar from Waste and Its Application in Water Treatment - Wang Hao (MATEC Web of Conferences)
With the drive of global environmental problems, the treatment of municipal waste has been emphasized. However, in recent years, the emergence of biochar technology has been a good way to deal with the problem of waste, and the rational use of biochar technology has become the key to solving the problem of waste. This paper analyzes in detail the types of municipal waste and the most popular biochar preparation technology. It discusses the raw materials of biochar from municipal waste and the application of biochar in water treatment and environmental protection. This paper discusses in detail the raw materials, preparation techniques, and related applications of biochar, aiming to provide a reasonable choice of methods for the related research and its applications in the field, to better solve the related problems. In the future, combining urban waste sorting and resource utilization technology, deeply integrating biochar production and environmental governance will have broad application prospects.